Voices of globalization - Wejnert, Barbara (Bingley, U.K. : Emerald, 2013)
This volume addresses issues of modern globalized development posing a question whether it symbolizes progress or regress for worlds societies. The papers focus on economic and political issues experienced by countries at this time of rapid diffusion of democracy and of the global market economy. A range of pertinent political issues are discussed, such as international migration, environmental protection and green energy, human rights, tolerance and equality, and economic justice. The concluding chapter provides a summary of presented topics in form of a discussion forum on outcomes of global development.
Political evolution, entrepreneurship, and autonomy : causes and consequences of an "axial" moment / Seth Abrutyn -- Another chapter from democracy's secret history : a research program on some small Spanish towns / John Markoff, Antonio Herrera -- Social movements, policy, and conflict in post-neoliberal Latin America : Bolivia in the time of Evo Morales / Eduardo Silva -- Post-conflict Georgian youth on conflict and tolerance / Tamar Dagargulia -- Freedom of religion and religiosity of evangelizers. Worldwide diffusion of religious movements and Polish schools of new evangelization / Waldemar Szlachetka -- Celebrities and politics : representation struggles in arenas of public intervention / Violaine Roussel -- From "Tippecanoe and Tyler, Too" to "Born in the U.S.A." : the transformation of the campaign song in presidential elections in the United States / Ashley Gromis -- Beyond the poverty paradigm : the neoliberal city and the low-income worker. The Buffalo, New York experience / Henry Louis Taylor, Linda McGlynn, D. Gavin Luter -- Signaling responsibility, deflecting controversy : strategic and institutional influences on the charitable giving of corporate foundations in the health sector / Edward T. Walker -- Participatory geographic information systems for environmental zoning plan : case study of the Madu Ganga estuary, Sri Lanka / Ram Alagan, Seela Aladuwaka -- Development of the atomic power industry in Poland : public debate on environmental conservation versus economic needs / Elzbieta Sawa-Czajka -- Reflections on the impact of globalization : diffusion, equality, and opportunities / Barbara Wejnert.
Includes bibliographical references and index.
Keywords: Social Science -- Sociology -- General; Globalization; Society & culture: general; Globalization; Political sociology